CSR disclosures in listed banks – current state and future perspective - Matuszak, Łukasz; Różańska, Ewa (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
The purpose of the paper is twofold. First, this study briefly analyzes the new non- -financial reporting requirements implemented in Polish Accounting Act. Second, it investigates the current state of CSR reporting in commercial banks listed on the Warsaw Stock Exchange and its connection with the new requirements. The sample consists of 12 banks. The data were collected in December 2016 covering three communication channels: annual reports (including management commentary), separate CSR reports in PDF files and information from the companies’ web sites. A content analysis and Likert scale were used to measure the level of CSR disclosures in five categories namely: environment, labor practices, human rights, community involvement and anti-corruption. Disclosures on business model was also examined. The results of the study show that banks prefer annuals reports rather than CSR reports or websites to communicate voluntary CSR disclosures. In most cases the disclosures in the areas: community involvement, environment and labor practices have already met the requirements of the amended Polish Accounting Act. The level of reporting in the areas: human rights and the fight against corruption is insufficient under the new regulations
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2017, Nr 478, s. 311-324
Keywords: non-financial information; CSR; banks; management commentary; informacje niefinansowe; banki; sprawozdanie z działalności